Endoplasmic Reticulum and cis-Golgi Localization of Human T-Lymphotropic Virus Type 1 p12(I): Association with Calreticulin and Calnexin - Ding, Wei (American Society for Microbiology, 2001)
Human T-lymphotropic virus type 1 (HTLV-1) is a complex retrovirus encoding regulatory and accessory genes in four open reading frames (ORF I to IV) of the pX region. We have demonstrated an important role of pX ORF I expression, which encodes p12(I), in establishment of HTLV-1 infection in a rabbit model and for optimal viral infectivity in quiescent primary lymphocytes. These data indicated that p12(I) may enhance lymphocyte activation and thereby promote virus infection. To further define the role of p12(I) in cell activation, we characterized the subcellular localization of p12(I) in transfected 293T cells and HeLa-Tat cells by multiple methods, including immunofluorescence confocal microscopy, electron microscopy, and subcellular fractionation. Herein, we demonstrate that p12(I) accumulates in the endoplasmic reticulum (ER) and cis-Golgi apparatus. The location of p12(I) was unchanged following treatments with both cycloheximide (blocking de novo protein synthesis) and brefeldin A (disrupting ER-to-Golgi protein transport), indicating that the protein is retained in the ER and cis-Golgi. Moreover, using coimmunoprecipitation assays, we identify the direct binding of p12(I) with both calreticulin and calnexin, resident ER proteins which regulate calcium storage. Our results indicate that p12(I) directly binds key regulatory proteins involved in calcium-mediated cell signaling and suggest a role of p12(I) in the establishment of HTLV-1 infection by activation of host cells.